Continuous teacher education in Russia : history, current practices and future directions - Valeeva, Roza A.; Kalimullin, Aydar M. (Emerald Publishing Limited, 2024)
Continuous Teacher Education in Russia examines the history, recent developments and direction of the modernization of continuous teacher education in Russia, providing a critical insight into the structure and development trajectory of teacher education and offers an analysis of the processes of change that are under way in Russia. Chapters authors discuss the complex system of continuous teacher training, starting with the history of Russia's teacher education since the 18th century until the present time. The general characteristics of continuous teacher education are then explored, followed by the role of pre-professional development of future teachers in pedagogical classes, the specific Russian phenomenon of the secondary vocational teacher education and the ways of assuring variability and flexibility of the higher teacher education in Russia. Special attention is also paid to the models of novice teacher induction in Russia and the issues of training highly qualified personnel in postgraduate and doctoral studies. This is the definitive English language text on continuous teacher education in Russia, drawing on scholarly expertise in Russia, locating the policies and practices that are discussed within the context of a global reform of teacher education and providing new perspectives that will be of interest to education scholars, policymakers and practitioners on an international scale.